2009
DOI: 10.1021/ma901336q
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Origin of Solvent Resistance of Polyacrylonitrile

Abstract: We report on the first in-situ sum frequency generation (SFG) spectroscopy characterization of polyacrylonitrile (PAN) interfacial interactions with air, sapphire, water, and heptane. Using the shift in the resonance frequency of CN at various interfaces, we demonstrated that PAN interacts with the surface hydroxyl of sapphire substrate through the lone pair orbital of nitrogen in the "end-on" configuration (σ-H bond). We also demonstrated that the CN-CN interaction is the main reason for the superior chemical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 26 publications
0
31
0
Order By: Relevance
“…This is due to the strong affinity between the CN-CN groups (within the polymer) compared to the CN-surface OH interactions. 19 We have also observed a shift in the CN peak due to the interactions of the CN group with the surface OH groups. The PIB is the most hydrophobic polymer that we have studied, and the small red shift of 30 cm -1 is similar to that of sapphire in contact with nonpolar pentadecane.…”
Section: Resultsmentioning
confidence: 61%
“…This is due to the strong affinity between the CN-CN groups (within the polymer) compared to the CN-surface OH interactions. 19 We have also observed a shift in the CN peak due to the interactions of the CN group with the surface OH groups. The PIB is the most hydrophobic polymer that we have studied, and the small red shift of 30 cm -1 is similar to that of sapphire in contact with nonpolar pentadecane.…”
Section: Resultsmentioning
confidence: 61%
“…Surface structures of polyacrylonitrile (PAN) at the buried PAN/sapphire interface were examined using SFG [173]. After annealing the sample for 8 h at 90 °C and then 4 h at 120 °C (above PAN T g of 80–100 °C), it was found that the SFG signal of the CN frequency shifted from 2242 cm −1 (probed by FTIR) in the bulk to 2254 cm −1 (probed by SFG).…”
Section: Buried Polymer/inorganic Solid and Polymer/polymer Interfmentioning
confidence: 99%
“…However, in the absence of water, nitrile groups will complex with sodium ion . Considering chemical properties of the nitrile group, this interaction can be attributed to the electron donating nature of the nitrile group …”
Section: Resultsmentioning
confidence: 99%
“…[48,49] Considering chemical properties of the nitrile group, this interaction can be attributed to the electron donating nature of the nitrile group. [2,21,50] Hence, in current studies, an attempt has been made in order to explain the role of the interactions between nitrile group and cations in the dissolution of PAN homo-polymer in [BMIM]Cl. This dissolution should be caused by the interruption and breaking of the dipolar-dipolar interactions of PAN [1,51] , and the formation of interactions between ÀCN group and 1-butyl-3-methylimidazolium cation [BMIM] + .…”
Section: Interactions Between Pan Molecules and [Bmim]clmentioning
confidence: 99%
See 1 more Smart Citation